Breeding waterfowl on British inland waters in 1980 - Tuite, C H; Owen, Myrfyn (Wildfowl, 1984)
This paper describes a survey of breeding waterfowl (ducks, geese, swans, rails and grebes) on enclosed inland waters in Britain in 1980. Data on numbers of adults, broods and young and on brood size, were collected from 448 sites with a wide geographical spread and representative of habitat types available. Information on the recreational activities taking place at each site and their intensity was also collected. Sixty percent of waters were natural lakes, 28% reservoirs, and 12% gravel pits. Reservoirs were the largest sites on average (45 ha) followed by gravel pits (33 ha) and natural waters (28 ha). Overall 40% of birds are on man-made habitats, but these are particularly important for Tufted Duck Aythya fuligula (51%), Coot Fulica atra (46%) and Great Crested Grebe Podiceps cristatus (60%). Mallard Anas platyrhynchos was by far the most widespread and numerous of the species, and occurred at the highest densities, followed by Coot, Tufted Duck and Canada Goose Branta canadensis. Density and productivity on British inland waters compared favourably with published figures for Scandinavia and North America. Details are given of density, productivity and breeding seasons of the commoner species. The number of adults counted was positively correlated with site area but area had no effect on either the number or density of young. In a comparison of matched sites surveyed in the mid-1960s, and an examination of Wildfowl Count trends for September, most species had increased their numbers since, and some very dramatically. Only one species, the Shoveler Anas clypeata, an uncommon breeder, had shown a noticeable decline in the survey comparison, but the reverse was true in all habitats.